The DmsABC Sulfoxide Reductase Supports Virulence in Non-typeable Haemophilus influenzae - Dhouib, Rabeb; Nasreen, Marufa; Othman, Dk Seti Maimonah Pg; Ellis, Daniel; Lee, Simon; Essilfie, Ama-Tawiah; Hansbro, Philip M.; McEwan, Alastair G.; Kappler, Ulrike (Frontiers in Microbiology, 2021)
Although molybdenum-containing enzymes are well-established as having a key role in bacterial respiration it is increasingly recognized that some may also support bacterial virulence. Here we show that DmsABC, a putative dimethylsulfoxide (DMSO) reductase, is required for fitness of the respiratory pathogen Haemophilus influenzae (Hi) in different models of infection. Expression of the dmsABCDE operon increased with decreasing oxygen availability, but despite this, a Hi2019dmsA strain did not show any defects in anaerobic growth on chemically defined medium (CDM), and viability was also unaffected. Although Hi2019dmsA exhibited increased biofilm formation in vitro and greater resistance to hypochlorite killing compared to the isogenic wild-type strain, its survival in contact with primary human neutrophils, in infections of cultured tissue cells or a mouse model of lung infection was reduced compared to Hi2019WT. The tissue cell infection model revealed a 2-fold decrease in intracellular survival, while in the mouse model of lung infection Hi2019dmsA was strongly attenuated and below detection levels at 48h post-inoculation. While Hi2019WT was recovered in approximately equal numbers from bronchoalveolar lavage fluid (BALF) and lung tissue, survival of Hi2019dmsA was reduced in lung tissue compared to BALF samples, indicating that the Hi2019dmsA had reduced access to or survival in the intracellular niche. Our data clearly indicate for the first time a role for DmsABC in H. influenzae infection, and that the conditions under which DmsABC is required in H. influenzae are closely linked to interactions with the host.